Translation Shift Analysis And Readability On Allegiant By Veronica Roth - Khansa, Amina, Dr. Dwi HaryantiM. Hum (2016)
This research focuses on the translation shift on Allegiant novel by Veronica Roth. The objectives of this research are (1) to classify translation shifts found in Allegiant Novel and its translation, and (2) to identify readability of translation shift applied in Allegiant Novel and its translation. The research type applied in this study is descriptive qualitative type. The object of the research is Allegiant novel written by Veronica Roth. The data are all utterances or sentences found on Allegiant novel written by Veronica Roth and its translation. The method of collecting data in this study is documentation and interviewing. The writer uses triangulation to prove the validity of the research. The results of this research shows that: first there are category shift 7,41%, intra-system shift 53,69%, level shift 7,02% and structural shift 31,79%. From the analysis the writer verifies each shift into some types. Category shift is divided into 3 types, there are noun into verb 0,42%, noun into adjective 0,09%, and verb into noun 6,89%. Intra-system shift is divided into 4 types, there are singular into plural 0,06%, verb into verb 42,00%, verb into verb phrase 0,51%, plural into singular 11.11%. Level shift is divided into 5 types, there are noun into noun phrase 2,25%, verb into verb phrase 1,70%, adjective into adjective phrase 0,30%, verb phrase into verb 2,64%, adjective phrase into adjective 0,03%. Structural shift is divided into 5 types, there are noun phrase into noun phrase 20,32%, noun phrase into noun 5,76%, clause into noun 0,91%, clause into clause 3,08%, sentence into sentence 1,70%. Based on the readability of translation shift above, there is readability of translation in Allegiant novel. Second, from 3275 data there are 3262 data has score 3 of readability or 99,60% and 13 data has score 2 or 0,39%. The finding shows that the readability level is high although the medium level also finds but it doesn't dominant. The high readability is more dominant for this translation. From the case above, it can be concluded that the target language in translation are readable because it is dominant with the high readability level. Keywords: translation, shift, readability.